Thermochronological insights into the thermotectonic evolution of Mishmi hills across the Dibang Valley, NE Himalayan Syntaxis. (1st April 2020) - Salvi, Dnyanada; Mathew, George; Kohn, Barry; Pande, Kanchan; Borgohain, Biraj
Graphical abstract: Highlights: First multi-thermochronometry results from Dibang Valley, Eastern Himalaya. Frontal zone cooled below 350 °C ca. 16 Ma, east of Hunli cooled ca. 16 - 13 Ma. Duplex initiated close to 8-9 Ma. LHS duplexing continued into Mid Pliocene. Detachment depth 5 km beneath Hunli. Maximum height 6 km above Hunli window. Abstract: Eastern Himalayan Syntaxis (EHS) that forms the northeastern termination of the Himalaya consists of three broad zones; Namche Barwa massif, Siang antiform and Mishmi Hills. The present work provides new in-situ apatite fission track (AFT), zircon (U-Th)/He (ZHe) and 40 Ar/ 39 Ar multi-thermochronometric ages across the Dibang valley in the Mishmi hills. The study constrains the structure, emplacement time of major thrusts and initiation of Lesser Himalayan Duplex (LHD). Biotite 40 Ar/ 39 Ar ages of the Lohit batholith suggest late Oligocene cooling. ZHe ages indicate late Miocene ( 8–9 Ma) foreland directed duplex initiation in the Dibang valley. The AFT cooling ages ( 5–3 Ma) suggest LHD continued into Mid Pliocene. Confined track lengths and thermal modelling indicate that the northeastern samples from the study area underwent a phase of rapid exhumation around 10 Ma, followed by slow cooling. It is in contrast to the south-western samples from the Dibang valley that have cooled and uplifted rapidly only after around 4 Ma, due to accelerated phase of LHD. Our 3D thermo-kinematic modelling of the data indicates less mass removal around Hunli than other parts of Dibang valley. The result is in contrast to previously estimated 16 km uplift near Hunli and mass removal. AFT ages from the Hunli window indicate that the region witnessed modest uplift of 4–5 km since ca. 4 Ma. Brittle duplexing of the lower LHS at Hunli and Mayodia caused the warping of the overlying litho-units. Hunli duplex alone accommodated 86% of the total shortening.